2003
DOI: 10.1017/s1355617703930062
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory functioning in Gulf War-era veterans: Relationships to war-zone duty, self-reported hazards exposures, and psychological distress

Abstract: To explore possible neurotoxic sequelae of Gulf War (GW) participation, olfactory identification performance, neurocognitive functioning, health perceptions, and emotional distress were assessed in 72 veterans deployed to the GW and 33 military personnel activated during the GW but not deployed to the war zone. Findings revealed that war-zone-exposed veterans reported more concerns about health, cognitive functioning, and depression than did their counterparts who did not see war-zone duty. There was no eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 63 publications
2
23
0
Order By: Relevance
“…To our knowledge, only one study assessed olfactory-related brain volume and reported reduced olfactory bulb volume in women with a history of childhood maltreatment (Croy et al, 2013). Other studies designed to assess clinical olfactory function in PTSD have been inconsistent (Croy et al, 2010, Dileo et al, 2008, Vasterling et al, 2000, Vasterling et al, 2003). However, recent preliminary data from our laboratory suggest that trauma-exposed combat veterans with and without PTSD may have a decreased ability to detect odors (Cortese et al, 2014), in addition to a self-reported reduction in general odor sensitivity (Cortese et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only one study assessed olfactory-related brain volume and reported reduced olfactory bulb volume in women with a history of childhood maltreatment (Croy et al, 2013). Other studies designed to assess clinical olfactory function in PTSD have been inconsistent (Croy et al, 2010, Dileo et al, 2008, Vasterling et al, 2000, Vasterling et al, 2003). However, recent preliminary data from our laboratory suggest that trauma-exposed combat veterans with and without PTSD may have a decreased ability to detect odors (Cortese et al, 2014), in addition to a self-reported reduction in general odor sensitivity (Cortese et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a series of neuropsychological studies of Gulf War veterans was undertaken some considerable time after deployment. [8][9][10] A review 11 of the results of these studies did not find a consistent pattern of significant deficits, and although certain subgroups (those who reported multiple symptoms and those who selfreported greater exposure to pesticides) had more deficits, again, there was no consistent pattern. Instead, the authors of the review concluded that these deficits were only mild and that "performance on objective tasks of neuropsychological function showed little correspondence to subjective perceptions of cognitive functioning."…”
mentioning
confidence: 96%
“…Similar question phrasing was used for National Health Survey, Iowa, and the VA Registry [38,48,136] and furthermore, National Health Survey and Iowa used the same three-point scale to describe the length of exposure [38,136]. Devens and a New Orleans subset also used identical tools to evaluate exposures [3,25,45]. Additional exposure information was gathered in three studies.…”
Section: Introductionmentioning
confidence: 99%
“…The most common of these were alcohol and tobacco use. Alcohol use was primarily evaluated using self-constructed questions about current drinking status, alcohol abuse, and number of drinks consumed [2,4,10,12,13,17,25,35,45,51,195,196]. However, Iowa, National Health Survey, and Millennium Cohort used validated instruments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation